The Downstream Effects of Bail and Pretrial Detention on Racial Disparities in Incarceration - Donnelly, Ellen A. (2018)
Bail and pretrial detention decisions may have important consequences for racial disparities in incarceration rates. Poor minority defendants who are unable to post bail and get released from jail before trial may be more likely to plead guilty and accept longer sentences of incarceration. Racial disparities in incarceration sentences may then reflect a combination of differences in the seriousness of a defendant’s case, criminal history, and economic resources to pay bail. This study examines the extent to which bail decision-making and pretrial detention explain Black-White disparities in criminal adjudications and sentences in the Delaware courts from 2012 to 2014. Over 80% of all criminal defendants have a bond imposed on them before their adjudication. Almost a third of cases involve pretrial detention. After controlling for measured differences in a variety of case characteristics, including severity of charges and criminal histories, cash-only bail and pretrial detention increase a defendant’s likelihood of conviction and pleading guilty, being incarcerated, and receiving a longer incarceration sentence. Bail and pretrial detention also contribute to 30% to 47% of the explained Black-White disparity in these court dispositions. Careful examination of cash-only bail, bail amount, and pretrial detention policies may help reduce racial disparities in incarceration